Do We Pay for Productivity? A Discussion of Policies to Encourage Academic Productivity in Colombia and Germany (2014)
This article discusses the advantages, disadvantages, motivations and problems associated to the pay-for-performance system implemented in order to incentivize scientific productivity in institutions of higher education. Based on a theoretical analysis within the framework of the economics of science, we analyze the discussions generated in Colombia and Germany with respect to the teacher`s remuneration systems. For Colombia we find an initial reaction of protest in the academic community against the reform established by decree 1279 of 2002. Whereas some academics criticize the decree`s merchandizing function, others request a wider range of activities to be taken into account for the variable component of their salary. On the other hand, in the discussion in Germany predominate those teachers that demand a reversion of the system, underlining the problems associated to the measurement of scientific production and the crowding-out of intrinsic motivation by extrinsic incentives. Taking into account the possible adverse effects of the pay-for-performance systems and the functions of higher education in society, we encourage a more profound reflection about incentivization systems in particular and the concept of scientific productivity in general.